Can tourism climatic indices reflect the impact of cold surges? - Dong, Yan; Xia, Lan (Geographica Pannonica, 2021)
Hibernation tourism in East and Southeast Asia is directly impacted by wintertime cold surges, which can result in high winds, extreme low temperatures, frost, freezing rain, and even sandstorms. This study compares two existing tourism climatic indexes—the Comprehensive Comfort Index (CCI) and the Tourism Climate Index (TCI)—to establish their ability to capture the full impact of cold surges on the tourism industry. From a climatic perspective, the TCI is more sensitive than the CCI, revealing a significant negative correlation with cold surge days. As illustrated here using a specific case study, the colder surge days in a month, the lower the TCI score for that month. This paper also evaluates potential reasons for the observed disparity between the two indices and proposes that the TCI exhibits a higher temperature standard and preference for long sunshine hours than does the CCI.
Keywords: Tourism Climate Index; Cold surge; Climate comfort; Hibernation tourism